Top pruning on seedlings rejuvenation: a tool for nurseries in Brazilian Atlantic Forest reforestation - Alexandre Hack Porto; Américo Wagner Júnior; Dionatan Gerber; Paula Helena Pereira O’Connor; Larissa Regina Topanotti; Claudemir Dantas da Silva; Murilo Lacerda Barddal; Izaclaudia Santana da Cruz; Fernando Campanhã Bechara (Acta Biológica Catarinense, 2021)
Plant nurseries produce many species simultaneously, which are often not used at the right time, remaining in the nurseries. These plants become aged and tall and, when planted in the field, often show poor performance, topple over, or die in degraded areas. This work aimed to evaluate the practice of drastic pruning in the rejuvenation of aged seedlings of native tree species for the restoration of the Atlantic Forest. Two tests (TA and TB) were conducted in southern Brazil, evaluating the relationship between pruning height × species and measuring regrowth and survival. In TA, 24 species (80%) had high survival (100%). Drastic pruning at 15- cm height generated greater regrowth heights compared to pruning at 30 cm for all species, but statistically only for 12 species. In TB, no differences were observed between pruning heights, but pruning at 15 cm and at collar level showed better values. It is recommended that seedlings be pruned for some species, to resume growth and to achieve a better height/diameter ratio in the nurseries and possibly to increase field survival, especially in degraded tropical areas, to be reforested.